Does Mining FDI Crowd in or Crowd Out Other Investments? A Cross-Country Investigation of FDI Intersectoral Linkages - Mendoza, Ronald U (Archīum Ateneo, 2013)
Foreign Direct Investment (FDI) in extractive industries (mining and quarrying) is expected to increase dramatically in many developing countries, due to the rising global demand for commodities. One key question for policymakers is whether this form of FDI could help spur investments in other sectors, in order to help boost their countries’ long term growth prospects. Countries with large extractive industries seek to promote economic diversification, so other types of FDI would also be critical in this regard. This paper analyzes whether mining FDI" crowds out" or" crowds in" FDI in other sectors via intersectoral linkages. It utilizes a novel data set covering sector-disaggregated FDI flows in 70 countries from 1985 to 2010. Results show differential effects of mining FDI on FDI in other sectors (manufacturing, services, financial services, non-financial services) and across country groups. Some of the interesting results are seen in the high income countries group, where mining FDI is observed to have crowding out effect on total services and more specifically, financial services FDI and in the lower middle income countries group, where mining FDI is observed to crowd in both manufacturing and financial services FDI.